Agricultura urbana e periurbana: abordagens socioambiental sobre hortas comunitárias no município de Cascavel - PR - Theinl, Terezinha Aparecida (2023)
Master’s thesis in Environmental Sciences at PPGCA – UNIOESTE analyzed the Urban and Peri-urban Agriculture Program with specific emphasis on urban community gardens in the Municipality of Cascavel / PR. There is a growing global concern about the number of people living in a state of moderate to severe food insecurity and suffering from the lack of access and availability of food in urban areas (FAO, 2019). The encouragement of Urban and Peri-urban Agriculture, based on agroecology, can be considered as a social, environmental, economic, and sustainable alternative, promoting the production and supply of food for urban populations. This research investigated the application of Law no. 6874 of July 16, 2018, which established the Municipal Program of Urban and Periurban Agriculture of the municipality of Cascavel - PMAUP. Thus, the question was asked: what are the advances and limits in the implementation of community gardens? What guidelines guided the urban and peri-urban agriculture program? Were the objectives of this program achieved? How was the implementation of community gardens developed? To answer these questions, the research used a bibliographic and documentary survey and consultation of the official platforms and websites of the Municipality of Cascavel. 08 questionnaires were applied to 06 horticulturists, 02 managers to collect information on the management of community gardens. Visits were made to the production units. For this study, three community gardens were chosen in the neighborhoods of Neva, Morumbi, Cascavel Velho/Veneza. It was a case study with the analysis of the implementation of Community Gardens. It is concluded that the implementation of community gardens was motivated by the need to present efficient alternatives related to vacant and idle land in public, private, community and residential spaces. This initiative reflects positively on the socio-environmental spheres promoted by the Municipal Program of Urban and Peri-urban Agriculture (PMAUP) in the city and is able to offer benefits both to the producers belonging to the community and to the surrounding society. It results in the production of healthy, pesticide-free food, generates income, social inclusion and the exercise of agroecology and sustainability.